Activation and Public Employment Services in Poland : Enhancing Labor Market Policies for the Out-of-Work Population - World Bank Group (World Bank, Washington, DC, 2018)
This policy note analyzes the profile of the out of work in Poland and compares this with the current set of labor market policies, in particular Public Employment Services. The note relied on existing data from the Polish Labor Force Survey, the tax and benefit model, expenditure data in Poland and the EU, qualitative and institutional analysis to prepare a profile of the out of work population, understand the various segments of vulnerable populations in need and the contrast it with the supply and quality of services for labor market support.